You Made El Team-O! The Transnational Browning of the National Basketball Association through the “Noche Latina” Marketing Campaigns - Moraga, Jorge E. (2015)
This essay pushes beyond the black-white binary in an effort to expand understandings into the relationship between sport, Latinidad, and global capitalism in the 21st century. Through a discursive analysis into the National Basketball Association (NBA) outreach policies, I ask: do recent shifts in the NBA’s marketing strategies, while alluding towards social inclusion and multicultural diversity, also contribute to the containment, exclusion, and marginalization to the fastest growing minority group in the United States: the Latina/o. By conducting a textual analysis into the NBA’s Noche Latina campaign, this essay makes the case that while the NBA may be another example of browning the sporting gaze the gaze remains fixed upon Western capitalist notions of identity and representation. An aim of this study seeks to highlight the contradictions within U.S. based-sport marketing in hopes that sport fans, pundits and academics alike might grapple with and strive towards understanding how phenomena like “Noche Latina” repackages racialized, sexist and cultural tropes for global television audiences and social media users alike.